Oral administration of crocin-loaded solid lipid nanoparticles inhibits neuroinflammation in a rat model of epileptic seizures by activating SIRT1 expression - Seyran Kakebaraei; Mohammadreza Gholami; Touraj Zamir Nasta; Elham Arkan; Fariborz Bahrehmand; Sajad Fakhri; Cyrus Jalili (Wolters Kluwer Medknow Publications, 2024)
Background and purpose: Epilepsy is a group of chronic neurological diseases caused by a complex set of neuronal hyper electrical activities and oxidative stress of neurons. Crocin is a natural bioactive agent of saffron with different pharmacological properties and low bioavailability. This study aimed to evaluate crocin-loaded solid lipid nanoparticles (SLNC) for neuroprotection activity and efficacy against pentylenetetrazol (PTZ)- induced epilepsy. Experimental approach: The rats were pretreated with SLNC and pure-crocin (PC; 25 and 50 mg/kg/day; P.O.) for 28 days before PTZ induction. Behavioral functions were evaluated by passive avoidance learning (PAL) tasks. Then, total antioxidant capacity (TAC), malondialdehyde (MDA), and pro-inflammatory factors were measured in the brain tissue using ELISA kits. Gene expression levels were analyzed with real-time polymerase chain reaction and immunohistochemical assay was used to assess the protein expression of sirtuin1 SIRT 1). Findings/Results: SLNC was prepared with an average particle size of 98.25 nm and 98.33% encapsulation efficiency. Memory deficit improved in rats treated with SLNC. Administering SLNC at 25 and 50 mg/kg significantly reduced MDA and proinflammatory cytokines while increasing TAC. Additionally, administering SLNC before treatment increased the levels of SIRT1, peroxisome proliferator-activated receptor coactivator 1α, cAMP-regulated enhancer binding protein, and brain-derived neurotrophic factor. Furthermore, SLNC administration resulted in the downregulation of caspase-3 and inflammation factor expression. Conclusion and implications: Overall, the obtained results showed that SLNC has better protective effects on oxidative stress in neurons, neurocognitive function, and anti-apoptotic and neuromodulatory activity than PC, suggesting that it is a promising therapeutic strategy for inhibiting seizures.